Socio-economic status, lifestyle and childhood obesity in Gombe. - Alkali YS; Ambe JP; Sabin M; Zacharin M (Nigerian Journal of Paediatrics, 2024)
Background: Childhood obesity is a complex condition resulting from an inter play of genetic predisposition, environmental factors and socio-economic status. The prevalence has been increasing all over the world, probably due to economic transition and rapid urbanization as well as globalisation. This relationship should be well established for Improved Health Planning in Gombe State and Nigeria.